RESEARCH ON THE FORMING LIMIT OF INCREMENTAL THERMAL FORMING OF MAGNESIUM ALLOY SHEET HEATED BY LIQUID MEDIUM - SHI PengTao; LI Yan; YANG MingShun; YAO ZiMeng (Jixie qiangdu)
Forming limit is an important performance index and process parameter in sheet metal processing. In this paper,A method for the thermal incremental forming of liquid while supporting and heating was proposed. An inverted cone was studied as a research object. The influence of process parameters such as the temperature,the distance between the layer and the diameter of the tool head on the thermal incremental forming was studied by means of orthogonal test,and the theoretical analysis is carried out. The results show that the forming limit angle increases obviously with the increase of the forming temperature,and the smaller the distance between the layers increases with the increase of the layer spacing. The limit angle of the tool head diameter is not significant.